Understanding the pharmacokinetics of Coartem(®) - Djimdé, Abdoulaye (BioMed Central, 2009)
Artemether and lumefantrine (AL), the active constituents of Coartem(® )exhibit complementary pharmacokinetic profiles. Artemether is absorbed quickly; peak concentrations of artemether and its main active metabolite, dihydroartemisinin (DHA) occur at approximately two hours post-dose, leading to a rapid reduction in asexual parasite mass and a prompt resolution of symptoms. Lumefantrine is absorbed and cleared more slowly (terminal elimination half-life 3-4 days in malaria patients), and accumulates with successive doses, acting to prevent recrudescence by destroying any residual parasites that remain after artemether and DHA have been cleared from the body. Food intake significantly enhances the bioavailability of both artemether and lumefantrine, an effect which is more apparent for the highly lipophilic lumefantrine. However, a meal with only a small amount of fat (1.6 g) is considered sufficient to achieve adequate exposure to lumefantrine. The pharmacokinetics of artemether or lumefantrine are similar in children, when dosed according to their body weight, compared with adults. No randomized study has compared the pharmacokinetics of either agent in pregnant versus non-pregnant women. Studies in healthy volunteers and in children with malaria have confirmed that the pharmacokinetic characteristics of crushed standard AL tablets and the newly-developed Coartem(® )Dispersible tablet formulation are similar. Studies to date in healthy volunteers have not identified any clinically relevant drug-drug interactions; data relating to concomitant administration of HIV therapies are limited. While dose-response analyses are difficult to undertake because of the low rate of treatment failures under AL, it appears that artemether and DHA exposure impact on parasite clearance time while lumefantrine exposure is associated with cure rate, consistent with their respective modes of action. In conclusion, knowledge of the pharmacokinetic profiles of artemether and lumefantrine is increasing within a range of settings, including infants and children. However, additional data would be warranted to better characterize artemether and lumefantrine pharmacokinetics in patients with hepatic impairment, in pregnant women, and in patients undergoing HIV/AIDS chemotherapy.